Loneliness and social isolation are associated with an increased risk of glaucoma: a UK Biobank cohort study - Xinyu Zhu; Bo Li; Xinyu Zhang; Yujin Jiang; Yikeng Huang; Chenxin Li; Zhi Zheng; Yili Zhang; Bei Zhu; Shuzhi Zhao (BMC, 2024)
Abstract Background Loneliness and social isolation have been found to be associated with various health-related outcomes. Our study aimed to evaluate the association of loneliness and social isolation with the risk of glaucoma. Methods A total of 373,330 participants from the UK Biobank without glaucoma at recruitment were included in this study. Self-reported questionnaires were used to define loneliness and social isolation. Incident glaucoma events were identified by hospital inpatient admissions and self-reported data. COX proportional hazards models adjusted for sociodemographic, lifestyle, and health-related factors were used to estimate hazard ratios (HRs) and 95% CIs. Results During a median follow-up of 13.1 (interquartile range: 12.3-13.9) years, 6,489 participants developed glaucoma. After adjusting for confounding factors, loneliness (yes vs. no: adjusted HR: 1.16; 95% CI: 1.04-1.30; P = 0.009) and social isolation (yes vs. no: adjusted HR: 1.08; 95% CI: 1.01-1.16; P = 0.033) were associated with an increased risk of glaucoma. Conclusions In this population-based prospective cohort study, loneliness and social isolation were associated with a higher risk of glaucoma.